2022
DOI: 10.1002/ddr.21918
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to minimize the effects of P‐glycoprotein in drug transport: A review

Abstract: P-glycoprotein (P-gp) is a transporter protein that is come under the ATP binding cassette family of proteins. It is situated on the surface of the intestine epithelium, where P-gp substrate binds to the transporter and is pumped into the intestine lumen by the ATP-driven energy-dependent process. In this review, we summarize the role of the P-gp efflux transporter situated on the intestine, the clinical importance of P-gp related drug interactions, and approaches to minimize the effect of P-gp in drug transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 201 publications
0
12
0
1
Order By: Relevance
“…Black pepper contains the flavonoid piperine. It has the capacity to function as a natural inhibitor of P-gp and CYP34A when co-administered and can boost the therapeutic efficacy of medications [1]. To induce this effect, the piperine dosage should be optimal and reach the minimal therapeutic concentration.…”
Section: The Kinetics Of P-gpmentioning
confidence: 99%
See 1 more Smart Citation
“…Black pepper contains the flavonoid piperine. It has the capacity to function as a natural inhibitor of P-gp and CYP34A when co-administered and can boost the therapeutic efficacy of medications [1]. To induce this effect, the piperine dosage should be optimal and reach the minimal therapeutic concentration.…”
Section: The Kinetics Of P-gpmentioning
confidence: 99%
“…The phenomenon known as drug resistance is responsible for the decrease in the restorative rate of most diseases as well as the loss in the therapeutic efficacy of most of the Life 2022, 12, 897. https://doi.org/10.3390/life12060897 https://www.mdpi.com/journal/life anticancer medications [1]. Treatment resistance is found not only to a single chemotherapeutic drug but to a diverse set of structurally and functionally distinct medicines.…”
Section: Introductionmentioning
confidence: 99%
“…One significant way the BBB interacts with pharmacological agents is through P-glycoprotein (P-gp), a transmembrane protein expressed on BMECs that functions as a drug efflux pump helping to eliminate potentially dangerous substances. Interestingly, drugs utilized in BD are known to have varying effects on P-gp function ( Husain et al., 2022 ). Notably, positron emission tomography studies in psychiatric patients have found increased P-gp function in the BBB ( de Klerk et al., 2010 ).…”
Section: The Bbb and Pharmacologic Implications In Bdmentioning
confidence: 99%
“…Whilst the Caco2 cells offer an efficient model to predict the passive permeability and active efflux in the intestine, the MDR1-MDCK cells express limited enzymes and basal transporter activity and hence more readily mimic the BBB (Colclough et al, 2019;Husain et al, 2022).…”
Section: In Vitro and In Vivo Evaluation Of P-gp Mediated Effluxmentioning
confidence: 99%